Strategy for Developing Quality Of Work Life To Enhance Employee Engagement at PT XYZ - Mastra, Chika Asgara; Novianti, Tanti; Suhendi, Suhendi (Indonesian Journal of Multidisciplinary Science, 2026)
This study examines the implementation of Quality of Work Life (QWL) factors to enhance employee engagement at PT XYZ. Using a quantitative descriptive approach with purposive sampling of 52 respondents comprising marketing and non-marketing employees, the research employed Importance Performance Analysis (IPA) and Chi-Square tests to evaluate the relationship between QWL factors and employee satisfaction. Results indicate that while employees demonstrate high intrinsic motivation and work satisfaction, collaborative communication and long-term commitment require improvement. IPA analysis revealed that career development and compensation are critical priorities for the marketing division, requiring immediate intervention, while communication, occupational health, and conflict resolution represent strengths that should be maintained. Chi-Square testing showed that most QWL factors have no significant relationship with employee tenure or education level, except for conflict resolution and workplace safety, which demonstrated significant correlations with employee profiles. The study concludes that strategic improvements in career development, compensation, workplace safety, and adaptive conflict resolution mechanisms are essential for enhancing employee engagement and reducing turnover rates at PT XYZ.